Computing The Effective Plastic Moment - Carskaddan, Phillip S.; Haaijer, Geerhard; Grubb, Michael A. (Engineering Journal, 1982)
The effective-plastic-moment approach does not exclude any shapes from plastic design; additionally, it permits plastic design methods to be employed in the rating of existing members. For plastic design, the most efficient distribution of material occurs when the effective flange yield strength is not below the actual compression flange yield strength. Furthermore, for a symmetrical section of a given depth, the effective plastic moment is optimum when 22.5% of the web area is moved from the web to the flanges, starting from a web area that makes the web fully effective. The effectiveplastic- moment approach is applicable to sections that are symmetric, unsymmetric, hybrid, and composite in negative bending.